Inhibition of viral and bacterial trigger-stimulated prostaglandin E2 by a throat lozenge containing flurbiprofen: An in vitro study using a human respiratory epithelial cell line. (September 2020) - Lambkin-Williams, Rob; Mann, Alex; Shephard, Adrian
Objectives: Symptoms of sore throat result from oropharyngeal inflammation, for which prostaglandin E2 is a key mediator. Flurbiprofen is a non-steroidal anti-inflammatory that provides sore throat relief. The preliminary objective of this study was to develop an in vitro model for assessing prostaglandin E2 stimulation by viral and bacterial triggers. The primary objective was to investigate the effect of diluted flurbiprofen-containing lozenges on prostaglandin E2 concentrations in stimulated cells. Methods: Prostaglandin E2 production was stimulated in three epithelial cell lines (A549, HEp2, and clonetics bronchial/tracheal epithelial) with influenza A virus (4.5 log10 tissue culture infectious dose50 /mL), or bacterial lipopolysaccharide (10µ g/mL) and peptidoglycan (3µ g/mL) and incubated overnight. Prostaglandin E2 levels were assessed by enzyme-linked immunosorbent assay up to 24 h after stimulation. The effect of flurbiprofen 8.75 mg lozenges (diluted to 0.44 mg/mL) on PGE2 production in stimulated cells was assessed in parallel; prior to viral/LPS/PEP stimulation of cells, 300 μL of test product or control was added and incubated for 30 s, 2 and 5 min (and 10 min for bacterial trigger). Prostaglandin E2 levels were measured following stimulation. Results: Viral and lipopolysaccharide/peptidoglycan infection did not consistently stimulate HEp2 cells and bronchial/tracheal epithelial cells to produce prostaglandin E2 . Influenza virus, and lipopolysaccharide/peptidoglycan stimulated high prostaglandin E2 concentrations in A549: mean prostaglandin E2 concentration 106.48 pg/mL with viral stimulation vs 33.82 pg/mL for uninfected cells; 83.84 pg/mL with lipopolysaccharide/peptidoglycan vs 71.96 pg/mL for uninfected cells. Flurbiprofen produced significant reductions in virus-stimulated prostaglandin E2 vs stimulated untreated cells at 2 min (p = 0.03). Flurbiprofen produced significant reductions in lipopolysaccharide/peptidoglycan-stimulated prostaglandin E2 concentrations from 30 s (p = 0.02), and at 2, 5 and 10 min (all p < 0.005) vs stimulated untreated cells. Conclusions: A549 cells provide a suitable model for assessment of prostaglandin E2 stimulation by viral and bacterial triggers. Diluted flurbiprofen-containing lozenges demonstrated rapid anti-inflammatory activity in viral- and lipopolysaccharide/peptidoglycan-stimulated A549 cells.